ANALISIS KELAYAKAN PEMBERIAN KREDIT KUR PADA PT BANK RAKYAT INDONESIA CABANG PINRANG - Wahyudi, Dicky (DECISION : Jurnal Ekonomi dan Bisnis, 2021)
This study aims to determine the standard procedures used in granting business loans to PT Bank BRI branch Pinrang district data collection techniques used in this study are field work research (Penelitian Lapangan), library research (Penelitian Kepustakaan), observation methods. The data analysis technicueused is descriptive qualitative. these are steps that should be taken into consideration by the analysis so that accurate data can be obtained accurately so that the bank is able to consider the appropriate amount of credit given to a prospective debtor based on his efforts.